Analysis of sounds made by Bos taurus and Bubalus bubalis dams to their calves - Lenner, Ádám; Papp, Zoltán Lajos; Komlósi, István (Frontiers in Veterinary Science, 2025)
Audio and video recording techniques have advanced significantly in recent years, allowing newer opportunities for sound analysis. The grouping of cattle breeds or individuals based on the connections between their behavior and condition and their vocalizations is important from the point of view of animal welfare. Despite the numerous studies published about the acoustic characteristics of such sounds, there has not been an acoustic analysis regarding of cattle behavior and condition in isolation. The grey cattle and domestic buffalo cows, separated from their calves for a few minutes, are stressed and vocalize orally. In this study various methods were employed for the analysis of the sounds that water buffalo and grey cattle made after weaning. Differences have been found between the two species, but not between individuals. Their pitch varies over time for both species. The buffalo voice is three times more dynamic than that of the grey cattle on a logHz scale. Furthermore, a significant difference was found between relevant mel frequency cepstral coefficients adapted to animals. Our findings may be utilized in agriculture and bioacoustic procedures.